Effects of Time Delay on the Performance of Harmonics Elimination in Active Power Filter - Thajeel, Ekhlas Mhawi; Hamdan, Daniyal; M. H., Sulaiman; Mazin Mustafa, Mahdi (Maxwell Scientific Publication Corp., 2015)
This study begins with a brief overview of the problem of harmonic distortion and its effect on the quality of electric power, how the active power filter mitigate this problems then investigate the effect of control circuit time delay on the performance of Active Power Filter (APF). Active filter is an electronic power system tha t absorbs harmonic currents in the network, generated by nonlinear loads. The nonlinear load seems the main source of harmonic distortion in the power system. A shunt active power filter with optimized PI discussed in this study. Delay times are inevitable in Digital Signal Processing (DSP) based controllers can significantly degrade the performance of active power filter. Active filter performance can be affected by the delay between the control and measurement of the output current of SAPF and load current harmonics. The proposed filter reduces harmonic distortion is within an acceptable range.